Relationship between chronic periodontitis and metabolic syndrome: a case-control study - Balagangadharan, Manovijay; Subramaniam, Deepa; Swaminathan, Mythili; Saranyan, Ravi; Kathiresan, Vel Latha; Arassappan, Raja (International Journal of Research in Medical Sciences, 2017)
Background: The aim of this case-control study was to investigate the periodontal status of patients with metabolic syndrome compared to general healthy individuals and to determine whether the periodontal status was consistent with the values of the metabolic components. Methods: A total of ninety patients were examined in this study. Group one consisted of forty five patients who were confirmed to have metabolic syndrome and group two consisted of forty five age and sex matched healthy controls. Plaque index, Gingival Bleeding Index (Ainamo & Bay), Probing Pocket Depth (PPD), Clinical Attachment Level (CEJ), total number of missing teeth and the reasons for extraction were also noted. Medical examination and blood investigations included measurement of height, weight, waist circumference, waist-hip ratio, Body-Mass Index (BMI), serum lipid profile, fasting blood glucose and blood pressure. Metabolic syndrome was defined according to NCEP ATP III definition. The results obtained were analyzed statistically using SYSTAT html output. Results: The results of the present study showed that the periodontal condition of group one patients were poor compared to group two patients. The periodontal conditioned worsened with an increase in the metabolic components. Conclusion: Based on the results of our study, it can be concluded that that periodontitis and metabolic syndrome were confounding the systemic effects of each other. Dentists should counsel their patients regarding the health hazards of metabolic syndrome and periodontitis and motivate them to maintain good oral hygiene and follow healthy life-style. Keywords: Chronic periodontitis, Metabolic syndrome (MS), Systemic diseases